Analisis Customer Preference dalam Memilih Hijab (Studi pada Produk Hijab Rumah Anita Jombang) - Kurniawan, Indra; Yuliana, Anita (Fakultas Ekonomi Universitas Samudra, 2025)
This research aims to identify variations or combinations of attributes that form customer preference for hijab in Jombang district. The method used is a descriptive-exploratory method. Data analysis uses conjoint analysis. The attribute factors that form customer preferences analyzed in this research are materials, colors, models and motifs. Sampling used accidental sampling technique, with a total of 100 respondents. The results show that the product combinations in hijab products of Rumah Anita that are consumer preferences are ceruty chiffon hijab material, soft hijab colors, pashmina hijab models and plain hijab motifs. In choosing Rumah Anita’s hijab products, the order of the most important attributes that influence consumer purchasing decisions is that the first is that consumers prioritize the model attribute, the second is the motif attribute, the third is the material attribute and the last is the color attribute.